Movement ecology of black marlin Istiompax indica in the Western Indian Ocean - Christoph A. Rohner; Roy Bealey; Bernerd M. Fulanda; Jason D. Everett; Anthony J. Richardson; Simon J. Pierce (Journal of Fish Biology, 2021)
The black marlin Istiompax indica is an apex marine predator and is susceptible to overfishing. The movement ecology of the species remains poorly known, particularly within the Indian Ocean, which has hampered assessment of their conservation status and fisheries management requirements. Here, we used pop‐up archival satellite tags to track I. indica movement and examine their dispersal. Forty‐nine tags were deployed off Kenya during both the north‐east (November–April) and south‐west (August–September) monsoon seasons, providing locations from every month of the year. Individual I. indica were highly mobile and track distance correlated with the duration of tag attachment. Mean track duration was 38 days and mean track distance was >1800 km. Individuals dispersed in several directions: north‐east into Somalian waters and up to northern Oman, east towards the Seychelles, and south into the Mozambique Channel. Their core habitat shifted seasonally and overlapped with areas of high productivity off Kenya, Somalia and Oman during the first half of the year. A second annual aggregation off the Kenyan coast, during August and September, did not coincide with high chlorophyll‐ a (chl‐ a ) concentrations or thermal fronts, and the drivers of the species' presence and movement from this second aggregation was unclear. We tested their habitat preferences by comparing environmental conditions at track locations to the conditions at locations along simulated tracks based on the empirical data. Observed I. indica preferred cooler water with higher chl‐ a concentrations and stayed closer to the coast than simulated tracks. The rapid and extensive dispersal of I. indica from Kenya suggests that there is likely a single stock in the Western Indian Ocean, with individuals swimming between areas of high commercial catches off northern Somalia and Oman, and artisanal and recreational fisheries catches throughout East Africa and Mozambique.

Movement and habitat use of striped marlin Kajikia audax in the Western Indian Ocean - Christoph A. Rohner; Roy Bealey; Bernerd M. Fulanda; Simon J. Pierce (Journal of Fish Biology, 2020)
Striped marlin Kajikia audax are globally Near Threatened and their stock in the Indian Ocean was last assessed as “overfished and subject to overfishing”. Significant gaps in our understanding of their ecology remain, hampering the efforts of fisheries managers to ensure stock sustainability. There is a particular lack of fisheries‐independent data. Here we present the results from the first large‐scale satellite tracking study of K. audax in the Indian Ocean. We tagged 49 K. audax with pop‐up archival satellite‐linked tags off the Kenyan coast from 2015 to 2019. Individuals were highly mobile, covering horizontal distances of up to 9187 km over periods ranging up to 183 days, with a mean daily distance of ~48 km. Long‐distance movements were recorded to the east and north of East Africa, with the most distant tracks extending north to the Arabian Sea and east to near the Maldives. None of the K. audax swam south of East Africa. Kernel utilization distributions of fish locations demonstrated their shifting seasonal activity hotspots. Over the sport‐fishing season (and tagging period) in Kenya, from December to March, K. audax typically stayed off the East African coast. After March, the activity hotspot shifted north to a region close to the Horn of Africa and Socotra Island. Remotely sensed sea surface temperature and chlorophyll‐ a maps indicated that this seasonal movement could be driven by a shift in prey availability. Our results show the high mobility of K. audax in the Western Indian Ocean, and that individuals seasonally range between two major fishing areas.

What constitutes effective governance of recreational fisheries?—A global review - Warren M. Potts; Nicola Downey‐Breedt; Pablo Obregon; Kieran Hyder; Roy Bealey; Warwick H. H. Sauer (Fish and Fisheries, 2020)
The effectiveness of recreational fisheries governance has been mixed, with some countries boasting good governance practices that sustain productive recreational fisheries, while others lack any policies and governance structures specific to recreational fisheries. Here, we identify what constitutes effective governance of recreational fisheries by carrying out: (a) a desktop review of 227 country‐specific fisheries legislation, policies and strategies; and (b) a follow‐up questionnaire‐based survey covering 57 contacts in 29 selected countries. Our results show that while recreational fishing is referred to in the main legislation of 67% of the countries reviewed, only 86 of these 152 countries provide a definition for either “recreational” or “sport” fishing and not always in the main legislation. Recreational fisheries are not considered to be effectively managed in many countries, with less than a quarter of respondents claiming that management in their country is effective. Furthermore, the management efficacy, including compliance with regulations, was considered greater for the industrial and small‐scale fishing sectors than for recreational fisheries in most countries. From our findings, it appears that effective recreational fisheries governance requires explicit acknowledgement of recreational fisheries with a clear legal definition in Policy, a well‐developed Policy statement, extensive co‐management processes, clearly defined biological, economic and social monitoring structures and efficient and transparent cost recovery mechanisms. To ensure adaptation to rapidly changing conditions, policy should recognize all fishery sectors and proactively incorporate adaptive planning and contingency plans to effectively secure the diverse values of resources for all users.